Piriformospora indica, a Cultivable Plant-Growth-Promoting Root Endophyte - Varma, Ajit (American Society for Microbiology, 1999)
Piriformospora indica (Hymenomycetes, Basidiomycota) is a newly described cultivable endophyte that colonizes roots. Inoculation with the fungus and application of fungal culture filtrate promotes plant growth and biomass production. Due to its ease of culture, this fungus provides a model organism for the study of beneficial plant-microbe interactions and a new tool for improving plant production systems.